Municipal fiscal stress, bankruptcies, and other financial emergencies - Guzman, Tatyana S.; Ermasova, Natalia (Routledge, 2023)
It is difficult to find someone who has not heard about the Puerto Rico, Detroit, Michigan, or Orange County, California bankruptcies. While guides for responsibly managing government finances exist, problems often originate not because of poor financial reporting or financial deficiencies, but because issues external to financial wellbeing arise, such as economic, demographic, political, legal, or even environmental factors. Exacerbating the problem, there is not much advice in the existing literature on how to act when municipalities face financial struggles. Filling this important gap, this book explores fiscal health and fiscal hardships, municipal defaults and bankruptcies, and many other aspects to help guide local governments during fiscal distress.